Statistical testing mediation in structural equations models variables with practical application - كمال غفران اسماعيل; جاسم بشرى سعد (Journal of Economics and Administrative Sciences, 2017)
Abstract: This study is studied one method of estimation and testing parameters mediating variables in a structural equations model SEM is causal steps method, in order to identify and know the variables that have indirect effects by estimating and testing mediation variables parameters by the above way and then applied to Iraq Women Integrated Social and Health Survey (I-WISH) for year 2011 from the Ministry of planning - Central statistical organization to identify if the variables having the effect of mediation in the model by the step causal methods by using AMOS program V.23, it was the independent variable X represents a phenomenon studied (cultural case of the man) and the mediation variable M_1 represents (women’s empowerment) and the mediation variable M_2 represents (the organizing of the family) and the dependent variable Y represents (violence against women), and the researchers found that the independent variable X affect the dependent variable Y indirectly through the mediation of one variable and the presence of any single mediation in the specimen.